Overview of Current Research on Artificial Intelligence in Logistics - Boršoša Patrik; Koman Gabriel (Logi, 2025)
This article aims to provide an overview of the current state of research on artificial intelligence in logistics, focusing on identifying key thematic areas addressed by the authors in this field. The article analyzes specific thematic areas that are the subject of individual studies dealing with this issue. Various methodological approaches were used in the analysis, including bibliometric analysis aimed at mapping the development of research and identifying key publications in the field of artificial intelligence in logistics. The PRISMA method was applied to select relevant sources, while qualitative content analysis was used for an in-depth evaluation of the studies’ content and for identifying the most frequently covered theoretical areas. The results show that research on artificial intelligence in logistics focuses on diverse thematic areas, such as digital transformation, sustainability and environmental aspects, process optimization within supply chains, and human-machine interaction. This article provides valuable insights for experts and practitioners in the field of logistics and serves as a foundation for further research in this dynamically evolving area.